2019
DOI: 10.1088/2053-1583/ab1518
|View full text |Cite
|
Sign up to set email alerts
|

Growth of multi-layered graphene on molybdenum catalyst by solid phase reaction with amorphous carbon

Abstract: A method to grow multi layers graphene (MLG) just by thermal annealing in an inert atmosphere is reported. A molybdenum (Mo) catalyst layer is used in combination with a solid amorphous carbon (a-C) source on top or below the Mo layer. The formation of MLG directly on top of the catalyst substrate surface is confirmed by Raman spectroscopy, atomic force microscopy, cross-section transmission electron microscopy, electron energy loss spectroscopy and x-ray photoelectron spectroscopy. Growth of MLG on top of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The average ratio I(D)/I(G) indicates the presence of some defects in the material [43,46,47,49,50]. In this letter, we mostly showed the power of the transfer-free process.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The average ratio I(D)/I(G) indicates the presence of some defects in the material [43,46,47,49,50]. In this letter, we mostly showed the power of the transfer-free process.…”
Section: Resultsmentioning
confidence: 74%
“…As catalyst metal, we used a molybdenum (Mo) film, a CMOS compatible metal, in order to overcome the disadvantages presented by copper [47]. Once the sacrificial Mo layer was etched, the terahertz transmission near-field imaging (TNFI) showed that the MLG film thoroughly lies on the oxidized silicon wafer (SiO 2 /Si).…”
Section: Introductionmentioning
confidence: 99%
“…Mo is chosen as a catalyst layer due to the possibility of growing thin and uniform layers of graphene because of its extremely low carbon solubility, thus creating a self-limiting growth process 55 . Moreover, the thermal expansion coefficient (CTE) of Mo in comparison with Cu and Ni is much closer to the one of Si, hence, Mo is less prone to wrinkle creation during high temperature graphene growth 56 , 57 . Additionally, catalyst residues are an important concern in an implantable device.…”
Section: Discussionmentioning
confidence: 99%
“…This method refers to preparing materials by using solid-state reactions [88] . In the solid-state reactions for forming amorphous catalysts, the spread and assembly of atoms or molecules can be realized by solid-phase diffusion or physically excited diffusion and aggregation.…”
Section: Solid Phase Methodsmentioning
confidence: 99%